Geographical Distribution Of Carcinoma Penis patients from Nepal: Retrospective analysis from a tertiary care cancer centre - Nepal, Umesh; Gharti, Binod Babu; Pokharel, Bharat Mani; Pandey, Greta; Adhikari, Pradipti; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2022)
Introduction: Carcinoma of Penis is not an uncommon disease in Nepal and comprises 1-10% of all the malignancies in males. The objective of this study is to retrospectively analyze the geographical distribution of these patients who visited Urology clinics at B P Koirala Memorial Cancer Hospital (BPKMCH), Bharatpur, Nepal during the specified time period.Materials and Methods:Altogether 183 patients from January 2012 to December 2016 with penile cancer were included. All others who had incomplete information about their address or those patients from neighboring countries were excluded. Data was collected and analyzed to find out the commonest provinces and districts in the country with the disease.Results: Madhesh Province also known as province No 2 was found to have the maximum disease burden. Out of the total 183 patients analysed, 87 were from Madhesh Province. The ratio of patients coming from this province was much more as compared to other provinces in the country. All the districts in this province showed a large disease burden with the maximum number of patients coming from Sarahi and Siraha districts. We did not receive any patient from Karnali Province during the specified time Period.Conclusions: Considering the fact that we are receiving a large number of patients from Madhesh province, we think we have to start educating the public in those districts. Regular early detection health camps to evaluate for any genital symptoms or lesions would have been beneficial. Educating them of hygiene, initiating vaccination programs would benefit. Remoteness of Karnali Province might have caused nil patient visiting for care. It can be proposed that government service and hospital services should reach these places to serve these remote areas.